Compression image sharing using DCT- Wavelet transform and coding by Blackely method - Ali Ahmed (Iraqi Journal for Computers and Informatics, 2017)
The increased use of computer and internet had been related to the wide use of multimedia information. The requirement for protecting this information has risen dramatically. To prevent the confidential information from being tampered with, one needs to apply some cryptographic techniques. Most of cryptographic strategies have one similar weak point that is the information is centralized. To overcome this drawback the secret sharing was introduced. It’s a technique to distribute a secret among a group of members, such that every member owns a share of the secret; but only a particular combination of shares could reveal the secret. Individual shares reveal nothing about the secret. The major challenge faces image secret sharing is the shadow size; that's the complete size of the lowest needed of shares for revealing is greater than the original secret file. So the core of this work is to use different transform coding strategies in order to get as much as possible the smallest share size. In this paper Compressive Sharing System for Images Using Transform Coding and Blackely Method based on transform coding illustration are introduced. The introduced compressive secret sharing scheme using an appropriate transform (Discrete cosine transform and Wavelet) are applied to de-correlate the image samples, then feeding the output (i.e., compressed image data) to the diffusion scheme which is applied to remove any statistical redundancy or bits of important attribute that will exist within the compressed stream and in the last the (k, n) threshold secret sharing scheme, where n is the number of generated shares and k is the minimum needed shares for revealing. For making a certain high security level, each produced share is passed through stream ciphering depends on an individual encryption key belongs to the shareholder.